PENGGUNAAN METODE VIRTUAL FIELD TRIP BERBANTUAN AUGMENTED REALITY TERHADAP KEMAMPUAN LITERASI BIODIVERSITAS SISWA PADA MATERI KEANEKARAGAMAN HAYATI - Rina Oktaviana (FKIP Universitas Tanjungpura, 2022)
The application of the Virtual Field Trip method plays a role in providing opportunities for students to be independent in their learning outside the classroom while increasing student motivation, reducing student stress; The important combination of these positive factors allows conceptual learning in Biology especially on biodiversity materials to be more effective in pandemic conditions. The purpose of implementing VFT is to replace conventional field trips, and introduce students to various aspects that are not easy to study directly for safety reasons, such as steep valleys and cost efficiency. Augmented Reality (AR) technology can incorporate 3D objects into a real environment. Biodiversity learning must involve students actively and use the surrounding environment as a learning resource with the ultimate goal of which is to increase literacy in biodiversity conservation. This is because biodiversity conservation literacy is included in scientific literacy which requires objective observation so as to encourage one's ability to understand various biodiversity, conservation efforts and communicate and apply conservation knowledge to solve problems that related to biodiversity issues